Vocal pain expression augmentation for a robopatient - Protpagorn, Namnueng; Lalitharatne, Thilina Dulantha; Costi, Leone; Iida, Fumiya (Frontiers in Robotics and AI, 2023)
Abdominal palpation is one of the basic but important physical examination methods used by physicians. Visual, auditory and haptic feedback from the patients are known to be the main sources of feedback they use in the diagnosis. However, learning to interpret this feedback and making accurate diagnosis require several years of training. Many abdominal palpation training simulators have been proposed to date, but very limited attempts have been reported in integrating vocal pain expressions into physical abdominal palpation simulators. Here, we present a vocal pain expression augmentation for a robopatient. The proposed robopatient is capable of providing real-time facial and vocal pain expressions based on the exerted palpation force and position on the abdominal phantom of the robopatient. A pilot study is conducted to test the proposed system and we show the potential of integrating vocal pain expressions to the robopatient. We highlight the advantages of proposed robopatient with real time vocal and facial pain expressions as a controllable simulator platform for abdominal palpation training studies.Finally we discuss the limitations of our proposed approach and suggest several future directions for improvements.